Effectivity of NS1 Antigen Test for Early Detection of Dengue Fever in Surakarta and Surrounding Areas - Setyaningrum, Arina; Saptawati, Leli; Sari, Yulia (Nexus Biomedika, 2015)
Background:.The first time of dengue virus infection can give symptoms as dengue fever. Dengue fever disease has symptoms that are not typical and may manifest as Dengue Hemorrhagic Fever and can progress to Dengue Shock Syndrome which can cause death if patients get treatment too late. Therefore, it is important to anticipate the delay in treatment so that requires a device to detection of dengue fever which is faster and more accurate. One is NS1 antigen detection methods. This study aimed to determine the effectiveness the NS1 antigen test for early detection of dengue fever in the region of Surakarta and surrounding areas. Method:.This study was a diagnostic test study using a community-based cross-sectional design. Sample size was 49 patients taken with consecutive techniques. Each samples performed detection of dengue NS1 antigen by Rapid strips test of immunochromatography and detection of genetic material of dengue virus by RT-PCR. Both of the data were tested with a diagnostic test. Result:.Diagnostic test results gave 67% of sensitivity, 89% of specificity, 67% of positive predictive value, 89% of negative predictive value, 6.09 of positive likelihood ratio, and 0.37 of negative likelihood ratio. The presence of a major change of the value of pretest probability (24%) to the value of the Post Test Probability (66%) indicated that the dengue NS1 antigen test device could provide diagnostic results which were important and useful. Conclusion:The NS1 antigen test is effective as diagnostic kit of Dengue virus infection due to its well specificity Keywords: Dengue Virus, Dengue NS1 antigen test, early detection of Dengue fever